Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan atau Penumpang Pesawat - Karno Karno (Fakultas Ekonomi Universitas Borobudur, 2014)
Researh titled Analysis of Service Quality Satisfaction Passenger Air Transportation. The primary data used 100 respondents from PT. Garuda, 30 respondents from PT Bouraqe, and 50 resondents from PT Lion. The study aims to determine the effectof service qality on customer satisfaction. By using the method of comparing the level of compliance with the level of service performance to the level of interest or customer expectations. The result showed that 86 percent concordance rate for the international flight (Garuda Airline) and 91 percent for thhe domestic flight.